New quill mites (Cheyletoidea: Syringophilidae) parasitizing tyrannid birds (Passeriformes: Tyrannidae) in Peru - Glowska, Eliza (Zootaxa, 2014)
Two new quill mite species (Cheyletoidea: Syringophilidae) are described from tyrannid birds (Passeriformes: Tyrannidae) in Peru: Picobia sayornis sp. nov. from the black phoebe Sayornis nigricans (Swainson) (first record of Picobia Haller species on tyrannid host) and Syringophilopsis szeffleri sp. nov. from the scale-crested pygmy-tyrant Lophotriccus pileatus (Tschudi). The Pacific elaenia Myiopagis subplacens (Sclater) is recorded as a new host for Syringophilopsis tyranni Bochkov and Galloway.